2008
DOI: 10.1016/j.rmed.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide: Independent effects of atopy, smoking, respiratory tract infection, gender and height

Abstract: Measurement of exhaled nitric oxide is widely used in respiratory research and clinical practice, especially in patients with asthma. However, interpretation is often difficult, due to common interfering factors, and little is known about interactions between factors. We assessed the influences and interactions of factors such as smoking, respiratory tract infections and respiratory allergy concerning exhaled nitric oxide values, with the aim to derive a scheme for adjustment. We studied 897 subjects (514 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 35 publications
9
98
3
5
Order By: Relevance
“…Statistically similar eNO initial values were measured for both low and high exposure tests (17.1 ± 6.3 and 15.8 ± 7.9, respectively). Such values were typical of non-atopic, non-smoking adults, whereas higher and lower values are expected for allergic and smoking subjects, respectively, as measured by Travers et al (2007), Dressel et al (2008). Similar eNO trends for high and low exposure scenarios were measured.…”
Section: Eno Resultssupporting
confidence: 69%
“…Statistically similar eNO initial values were measured for both low and high exposure tests (17.1 ± 6.3 and 15.8 ± 7.9, respectively). Such values were typical of non-atopic, non-smoking adults, whereas higher and lower values are expected for allergic and smoking subjects, respectively, as measured by Travers et al (2007), Dressel et al (2008). Similar eNO trends for high and low exposure scenarios were measured.…”
Section: Eno Resultssupporting
confidence: 69%
“…There were studies that assessed the reference equations of FeNO in healthy adults and, among these studies [14][15][16][17][18], only one involved healthy nonsmoking adults as in our study [14]. Many studies involved subjects who were current smokers or ex-smokers, with airway diseases or respiratory tract infections [15,16,18,21,22]. For example, a study from Germany included current smokers, asthma subjects and subjects with respiratory tract infections (in 24.3%, 3.8% and 20.2%, respectively, among the 897 subjects) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on reference values of FeNO in the general population were mainly limited to children [11][12][13]. There are limited data on the reference value of FeNO in the adult population [14][15][16][17][18], and there is very limited information on FeNO in a healthy, nonsmoking Chinese population. FeNO is a promising noninvasive marker for the assessment of airway inflammation, especially for asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Although duration of rhinitis does not seem to be an important factor in determining elevated FeNO, severity and seasonality of rhinitis as well as coexisting asthma and ocular symptoms were found to be associated with FeNO, in our atopic and nonatopic patients. Dressel et al suggested that respiratory allergy, smoking, respiratory tract infection, male gender, and height are independent factors of increased FeNO levels, 23 and others explained the association between FeNO and gender by differences in height. 24 Conversely, gender, but not height, has been reported as a determinant of FeNO in adults.…”
Section: Discussionmentioning
confidence: 99%